Medical innovations and health inequalities: sexual and reproductive health put to the test of facts - (:unkn) unknown (My University, 2013)
http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2178 Panel Medical innovations and health inequalities: sexual and reproductive health put to the test of facts, mod. Chrystelle Grenier-Torres
Keywords: African Research